Pengaruh Kepuasan Kerja dan Beban Kerja Terhadap Kinerja Karyawan pada BT Batik Trusmi - Aan Kanivia; Ni Wayan Fitriana Ayu Lestari; Nurmaulana Rifki Abdullah (Jurnal EBI, 2021)
This study discusses how job satisfaction and workload affect employee performance at BT Batik Trusmi. The purpose of this study is to identify job satisfaction and workload that can affect employee performance at BT Batik Trusmi. The sampling technique used a questionnaire with a total of 80 respondents who are employees of BT Batik Trusmi. The independent variable in this study (X1) job satisfaction (X2) workload, while the dependent variable in this study is employee performance (Y). The analytical test tool used is SPSS 20 multiple regression analysis method. The results are  job satisfaction has a positive effect on employee performance at BT Batik Trusmi, workload has a positive effect on employee performance at BT Batik Trusmi and job satisfaction and workload simultaneously have a positive influence on employee performance at BT Batik Trusmi.